Efficacy of Indigenous Botanical Pesticides Against Thrips tabaci on Onion: Efficacy of Pesticides on Onion (Biological Sciences - PJSIR, 2023)
Thrips tabaci L. is a polyphagous pest of various crops including onions. It has caused considerable losses to onion production as it has developed resistance against many synthetic pesticides. Moreover, pesticides used are hazardous to humans and environment. Therefore, the effectiveness of four indigenous botanical pesticides i.e., neem (Azadirachta indica A. Juss.), nazboo I sweet Basil (Ocimum basilicum L.), zangi I nerium (Nerium Oleander L.), Aloevera (Aloevera L.) Burm. f., along with Pirate (Chlorfenapyre) as positive and water as control negative were evaluated against T. tabaci. The data was recorded before application and after 24, 48, 72, 96 h and 7 days of spray. Based on the population of T. tabaci, two sprays were done in the study. After the first spray, maximum population reduction of T. tabaci was recorded in pirate (97.62%) after 48 h of spray, followed by 81.83% and 74.52% reduction in aloe vera and neem treatments after 96 and 72 h of spray. A similar trend was observed after second spray, as maximum T. tabaci population reduction was recorded in pirate (94.79%), followed by Aloevera (83.06%) and neem (78.0%) treatments. Nazboo and zangi were least significant in controlling T. tabaci. Moreover, the highest onion yield was recorded in pirate treatment that was not significantly different from yield in Aloevera treatment, whereas lowest yield was obtained in control followed by nazboo and zangi treatments. Therefore, it is recommended that Aloevera should be included for the management of T. tabaci in onions.